Methodological comparison of the allele refractory mutation system and direct sequencing for detecting EGFR mutations in NSCLC, and the association of EGFR mutations with patient characteristics - Wu, Minmin; Pan, Xiaodong; Xu, Yaya; Wu, Siying; Wu, Xiuling; Chen, Bicheng (Oncology letters, 2018)
Gefitinib is effective for patients with non-small cell lung cancer (NSCLC) with a mutation in the epidermal growth factor receptor (EGFR) gene, which makes the detection of EGFR mutations a critical step prior to determining a treatment schedule. Therefore, the present study determined the EGFR mutation status in patients with NSCLC using an allele refractory mutation system (ARMS) and analyzed the detection ratio for different specimen types. A total of 1,596 NSCLS samples were collected and EGFR gene mutations were detected on exons 18-21 using ARMS and direct sequencing. The concordance of two methods reached 89.21%, with a total mutation rate of 45.55% (727/1,596), in which the mutation rate in lung adenocarcinoma samples was markedly increased compared with squamous cell carcinoma (51.77 vs. 8.68%). In patients with lung adenocarcinoma, EGFR mutations were more frequent in female patients than male patients (65.53 vs. 39.80%, P<0.01); there was no observable difference depending on age. Similar results were obtained for squamous cell carcinoma. In the present study, certain rare mutations were also identified; these may be subjects for further study. The impact of different sample types on the consistency between the methods was determined to be insignificant. ARMS is a more applicable approach for large-scale clinical detection than direct sequencing, and we hypothesize that ARMS may replace direct sequencing if the drawbacks of ARMS, including its narrow detection range, can be amended.